(untitled) - 1948 Oct. 29-; Davis, David; Camling, Candace (Gretna, La., 2011)
Presents a Texas twist to classic Christmas tune, from a mockingbird in a gum tree to twelve longhorns leaping.
Keywords: Juvenile poetry; Poetry; Christmas; Poetry; Gifts; Gifts; Texas; Juvenile poetry; Christmas; Texas; Children's poetry, American; American poetry